(untitled) (Journal of Parents and Teachers, 2014)
In this article, Mª José Díaz-Aguado is interviewed, who begins by explaining the characteristics of harassment and the patterns of action that teachers must follow. In addition, it exposes a non-violence program to educate students in social skills and in the peaceful resolution of conflicts. Finally, it also speaks of authority, discipline and collaboration between family and school in this area.